Therapeutic exercises as a component of physical habilitation of Charcot–Marie–Tooth disease - N. A. Shnayder; S. I. Goncharova; D. P. Dzyuba (Нервно-мышечные болезни)
Therapeutic physical culture (physical therapy) is an integral part of the programs of habilitation and rehabilitation in many diseases, includingdiseases of central and peripheral nervous system. Charcot-Marie-Tooth disease (CМТ) is a hereditary degenerative disease peripheral nervous system accompanied by the development of progressive muscle weakness and persistent movement disorders. Currently, the use of specialized complexes physical therapy helps to maintain the functional state of the muscles and musculoskeletal status of patients with CMT, and improve strength endurance and increase daily physical activity of the patients. This article describes the modern approaches to organization of physical therapy sessions, recommendations on the training regime, the main types of exercises used in this disease in University Clinic.